Penerapan Algoritma Apriori Pada Prediksi Penjualan Tanaman Hias Bromelia (Studi Kasus: Karimah Flora) - Mufidah Karimah; Wulan Pahira (Teknik Informatika Universitas Pamulang, 2022)
Apriori algorithms are part of the algorithms in data mining which are often used to find data patterns. Apriori algorithms are often used in sales transaction data. In this study, the authors discussed the application of apriori to the prediction of sales of ornamental bromeliads. The author found that one of the problems is often taking care of plants. Of course this reduces the revenue at the Karimah Flora shop. From these problems the authors conducted research on sales transaction data in the last 3 months of 2020, namely August, September and October. Then the authors collect data on the sale of ornamental plants bromeliads which will then be calculated by applying the a priori algorithm formula. The calculation determines which of the 21 types of ornamental plants bromeliads will be studied, after which the authors conduct an analysis for order combination patterns of up to 4-itemsets, so that they can form an association rule. By applying the algorithm in this study, it produces a combination of ornamental bromeliads to attract consumers to buy promotional packages offered according to the pattern.